2018
DOI: 10.1002/app5.222
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Tobacco Control in Singapore: Lessons and Challenges in the Implementation of the Framework Convention on Tobacco Control

Abstract: Singapore has implemented tobacco control policies since the 1970s, more than three decades before it became party to the World Health Organization (WHO) Framework Convention on Tobacco Control-the first evidence-based global health treaty in 2005. The country's stringent policies have resulted in a 13 per cent adult smoking prevalence rate, one of the lowest in the world. This article reviews how a mix of demand-and supplyreduction measures with extensive regulation and stringent enforcement has contributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Our study showed that only 44% of the smokers were aware of the institutional smoking cessation programmes for psychiatric patients and only 4% were enrolled in the programmes at the time of the interview. Singapore has one of the most effective strategies for treatment of tobacco dependence with a range of smoking cessation services embedded in the community, schools, and workplaces [55]. Healthcare institutions have cessation clinics to integrate smoking cessation with clinical management, especially for the vulnerable groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study showed that only 44% of the smokers were aware of the institutional smoking cessation programmes for psychiatric patients and only 4% were enrolled in the programmes at the time of the interview. Singapore has one of the most effective strategies for treatment of tobacco dependence with a range of smoking cessation services embedded in the community, schools, and workplaces [55]. Healthcare institutions have cessation clinics to integrate smoking cessation with clinical management, especially for the vulnerable groups.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare institutions have cessation clinics to integrate smoking cessation with clinical management, especially for the vulnerable groups. The hospital based smoking cessation programmes in Singapore include pharmacotherapy and behavioural therapy (counselling and tele-support) with an intent to achieve 20% to 36% quit rates [43,55]. The treatment is patient specific, based on their medical history, sociodemographic factors, lifestyle factors and psychiatric conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Singapore is a city-state located in Southeast Asia with a multi-ethnic population and was among the first 40 countries to ratify the FCTC. It exercises stringent smoking policies and extensive regulations on the demand and supply of tobacco 12. In the nationwide Singapore Mental Health Study conducted in 2010(SMHS 2010), Picco and colleagues13 reported local smoking prevalence rates of 16%.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in 2015 Singapore banned emerging tobacco products including e-cigarettes and devices that are smoked or mimic smoking. 67 ’ In Australia, nicotine is a scheduled poison, so products containing nicotine for human consumption are prohibited unless for ‘human therapeutic use’ (cigarettes are grandfathered). 68…”
Section: Regulation Of Htps In Fctc Party Countriesmentioning
confidence: 99%